PEMANCAR AM STEREO - Amir, Ardi (MEKTEK, 2011)
In this project created an AM STEREO transmitter that the signal can be received on receiving AM MONOand AM STEREO. To obtain broadcast quality, should be using the receiver AM STEREO. The advantages ofthis transmitter broadcasts a bit cleaner when compared with AM MONO, but the transmitter AM STEREOwas not hifi when compared with STEREO FM transmitter. Transmitter consists of four sections of the mostimportant are:-Isolator-Matrix Audio-Phase Modulator-Amplitude Modulator